Keragaman jenis dan persen penutupan tumbuhan air di ekosistem Danau Laut Tawar, Takengon, Provinsi Aceh - Irma Dewiyanti (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. Primary production in freshwater can be observed with the existing of aquatic plants includes micro and macrophyte. The study of aquatic plant is necessary due to the plant has important in aquatic environments, such as providing habitat, spawning ground, feeding ground, and nursery ground for aquatic biota. This study was conducted in June 2012, and the purposes were to identify species of aquatic plants and their percent cover in Lake Laut Tawar, Takengon. Sampling were conducted using quadrate transects of 0.5 x 0.5 m2, and the every transect was divided into 25 sampling points. A total of 10 species of aquatic plants were found and there were divided into four groups based on their morpho-ecology i.e. emergent, free floating, free submerged and rooted with floating leaves. Of these, emergent group was the most predominant (six species), followed by free floating (two species), free submerged (one species), and rooted with floating leave (one species). Hydrilla verticillata (free submerged group) and Eichhornia crassipes (free floating group) had the highest percent covers and density.